2018
DOI: 10.1007/s00348-018-2537-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of forces applied by liquid water drops at high drop velocities impacting a glass plate with and without a shallow water layer using wavelet deconvolution

Abstract: Time-dependent forces applied by 2 and 4.5 mm diameter drops of water (with velocities up to terminal velocity) impacting upon a glass plate with or without a water layer (up to 10 mm depth) have been measured using two different approaches, force transduction and wavelet deconvolution. Both approaches are in close agreement for drops falling on dry glass. However, only the wavelet approach is able to measure natural features of the splash on shallow water layers that impart forces to the plate after the initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…As mentioned previously, Yu and Hopkins [19] have shown that a thin film of water on the impact surface may affect the impact force. We do not account for this effect here, although we note that in our experience during testing on surfaces at low angles of incidence, the impact surface remained slightly wet such that small puddles sometimes formed close to some droplet impact locations.…”
Section: Theoretical Model For the Sound Power Produced By Droplet Impacts On A Flat Panelmentioning
confidence: 70%
See 3 more Smart Citations
“…As mentioned previously, Yu and Hopkins [19] have shown that a thin film of water on the impact surface may affect the impact force. We do not account for this effect here, although we note that in our experience during testing on surfaces at low angles of incidence, the impact surface remained slightly wet such that small puddles sometimes formed close to some droplet impact locations.…”
Section: Theoretical Model For the Sound Power Produced By Droplet Impacts On A Flat Panelmentioning
confidence: 70%
“…Yu and Hopkins [19] measured the impact velocity for 2 mm diameter and 4.5 mm diameter water droplets falling in air from various heights between 0.41 m and 15 m. They compared their measurements with those predicted using the empirical model of Range and Feuillebois [33] which gives the impact velocity 0 , for a droplet with diameter , density and viscosity falling through air with density from a height as…”
Section: Droplet Size Shape and Impact Velocitymentioning
confidence: 99%
See 2 more Smart Citations
“…In the study of Ref. (Yu and Hopkins, 2018), an accelerometer array was used to measure the impact force when a droplet impacted on a liquidfilm wall. Their experimental results showed that for the same droplet impacting on different wet walls at the same impact velocity, the impulses of the impact forces may differ considerably.…”
Section: Validation Of Experimental Measuring Methodsmentioning
confidence: 99%